The role of negative magnetic resonance imaging: can we safely avoid biopsy in P.I.-R.A.D.S. 2 as in P.I.-R.A.D.S. 1?. (2nd January 2019) - Regis, Lucas; Celma, Ana; Planas, Jacques; Lopez, Ricardo; Roche, Sarai; Lorente, David; Placer, Jose; Trilla, Enrique; Morote, Juan
Abstract: Purpose: It remains unclear whether patients with prostate cancer suspicion and negative magnetic resonance imaging (M.R.I.) can safely obviate biopsy. The purpose of this study was to assess the clinical negative predictive value (N.P.V.) of M.R.I. in excluding prostate cancer. The secondary end-point was to compare N.P.V. to detect significant prostate cancer of M.R.I.The secondary end-point was to compare N.P.V. to detect significant prostate cancer in M.R.I. classified as P.I.-R.A.D.S.1 and as P.I.-R.A.D.S.2 Methods: From December 2012 to January 2017, 1128 M.R.I.s were performed consecutively due to prostate cancer clinical suspicion. The absence of suspicious and presence of low-risk areas were considered as negative M.R.I., P.I.-R.A.D.S.1 and 2. Biopsy results were compared according to P.I.-R.A.D.S. classification. The clinically significant disease was defined as International Society of Urological Pathology group higher than 1. Results: Two hundred and twenty-two (20%) M.R.I.s didn't highlight targetable imaging suspicious areas, which were recorded as negative tests: 130 (59%) P.I.-R.A.D.S.1 and 92 (41%) P.I.-R.A.D.S.2. Detection of clinically significant prostate cancer in at least one biopsy core was higher in the P.I.-R.A.D.S.2 group, 9% (8/92) vs 3% (4/130), p = 0.047. The N.P.V. in biopsy-naïve men and P.I.-R.A.D.S.1 was 95% for significant disease, while in patients subjected to repeated biopsies and P.I.-R.A.D.S.1, the N.P.V. found was 99%. Those rates differ from the P.I.-R.A.D.S.2 group: N.P.V. in biopsy-naïve patients was 84%, and 95% in repeated biopsy. Conclusions: P.I.-R.A.D.S.2 shouldn't be considered as a negative M.R.I. A biopsy cannot be routinely omitted in biopsy-naïve men with clinical suspicion of cancer and a low-suspicious area in M.R.I., giving the possibility of missing clinically significant tumors.